Sex and gender differences in job attribute preferences: Exploring the role of gender self-schemas - Southey, Olivia Cara (Organisational Psychology, 2022)
Recruitment strategies to promote gender diversity and equality seek to attract job applicants based on their sex. Individuals differ in terms of what they find attractive in jobs, called job attribute preferences (JAPs), and these preferences may vary according to sex. Job attribute preferences can include, for example, pay, type of work or flexible hours. Previous studies investigating differences in JAPs using biological sex as comparison variable have, however, provided contradictory findings. The focal research question of this study therefore investigates whether men and women, according to their biological sex, express different JAPs. Furthermore, this study interrogates the use of biological sex as the measured variable to differentiate applicants. Using gender self-schema theory, this study incorporates gender self identification as an additional operationalisation for sex. Gender self-identification is used to determine firstly, whether an individual's biological sex and gender self-identification align (measured using Bem's Sex Role Inventory (BSRI)). Secondly, this study investigates differences in JAPs using gender self-identification rather than biological sex to compare and contrast findings. In this cross-sectional study, a non-probability convenience sampling approach was used to survey 413 respondents across both a student and a field sample. Findings indicate that there were few significant differences in JAPs between men and women using biological sex. Moreover, interestingly, participants' gender self-identification (as per the BSRI) only partially aligned with their biological sex. Finally, JAPs found to be significantly different between males and females increased when gender self-identification was used as the variable to measure sex. These findings are useful for recruitment and selection as they reveal that job attributes could be more gender specific than found in past studies. The finding that gender self-identification did not align with biological sex is important as it challenges the conceptualisation of biological sex as a demographic variable. Furthermore, the results challenge findings from past studies on the link between JAPs and sex. The results suggest that gender, rather than biological sex, should be used – or at least interrogated further - in future research.